(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Symptoms of wood pocket disease of lime on Bearss lime trees (IVIA 124),kept in Shambat Research Station, Khartoum State, Sudan were described. These wereyellowing of foliage and death of branches, in addition to sectoring of fruits, brownstreaks on fruits and finally the death of the tree. Death of several potted seedlings wasalso observed, irrespective of the rootstock, accompanied by suckering of the rootstock.Branches showed cracking and wood staining with dark substance, typical symptoms ofwood pocket. As the disease is a genetic disorder, clones of Bearss lime tolerant towood pocket should be introduced and evaluated under Sudan conditions. This is thefirst record of wood pocket disease of lime in Sudan.